2018
DOI: 10.3389/fmicb.2018.01310
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Hemolysin Is Regulated Under the Collective Actions of HapR, Fur, and HlyU in Vibrio cholerae El Tor Serogroup O1

Abstract: The biotype El Tor of serogroup O1 and most of the non-O1/non-O139 strains of Vibrio cholerae can produce an extracellular pore-forming toxin known as cholera hemolysin (HlyA). Expression of HlyA has been previously reported to be regulated by the quorum sensing (QS) and the regulatory proteins HlyU and Fur, but lacks the direct evidence for their binding to the promoter of hlyA. In the present work, we showed that the QS regulator HapR, along with Fur and HlyU, regulates the transcription of hlyA in V. choler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 59 publications
3
29
0
Order By: Relevance
“…Fur coordinates with HapR to tightly regulate tcpP, toxT, and tcpA, leading to the cell density transcriptional manner of expression of these genes. HapR repression of Fur (Gao et al, 2018), AphA activation of tcpP (Kovacikova and Skorupski, 2001;Kovacikova et al, 2004), TcpP activation of toxT (Krukonis et al, 2000), autoregulation of Fur (Lee et al, 2007), and ToxT activation of tcpA (DiRita et al, 1991) were reported by other researchers. LCD, low cell density; MCD, medium cell density; HCD, high cell density.…”
Section: Introductionmentioning
confidence: 62%
See 4 more Smart Citations
“…Fur coordinates with HapR to tightly regulate tcpP, toxT, and tcpA, leading to the cell density transcriptional manner of expression of these genes. HapR repression of Fur (Gao et al, 2018), AphA activation of tcpP (Kovacikova and Skorupski, 2001;Kovacikova et al, 2004), TcpP activation of toxT (Krukonis et al, 2000), autoregulation of Fur (Lee et al, 2007), and ToxT activation of tcpA (DiRita et al, 1991) were reported by other researchers. LCD, low cell density; MCD, medium cell density; HCD, high cell density.…”
Section: Introductionmentioning
confidence: 62%
“…Vibrio cholerae El Tor serogroup O1 strain C7258 (Peru, 1991) was used as the derivative (wild type, WT). Non-polar fur and hapR single-gene deletion mutants fur and hapR derived from the WT strain were constructed in our previous study (Gao et al, 2018). The deletion mutant of lacZ (designated as lacZ) was constructed from WT by homologous recombination using the suicide plasmid pWM91, which was similarly performed as previously described (Wu et al, 2015).…”
Section: Bacterial Strains and Cultural Conditionsmentioning
confidence: 99%
See 3 more Smart Citations